If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3j + 4 = 10 Reorder the terms: 4 + 3j = 10 Solving 4 + 3j = 10 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3j = 10 + -4 Combine like terms: 4 + -4 = 0 0 + 3j = 10 + -4 3j = 10 + -4 Combine like terms: 10 + -4 = 6 3j = 6 Divide each side by '3'. j = 2 Simplifying j = 2
| 201=17b+99 | | 6=2-b | | 3(-2-3x)=9x | | 20x+240=240 | | 33x-8-14x=10 | | 8x-8=15x-21 | | 2d+18=2-6(d+7) | | =8.041840047611249e+17 | | 5=1-a | | 0.2s=16 | | =0.2e+17 | | 92=c+3 | | 4x^2+5x-440=0 | | 220=-12.5x | | P+-3=5 | | -35+9= | | 32x+12y+52= | | 0.15-1.8=0.3(x-5) | | 8-7x-4=-57+5x-11 | | 8z+5=8 | | C+-6=-10 | | ln(6x+14)=2 | | 25x^2-30x=72 | | -x-15=x-5 | | f(x)=3+0.1x | | 3x-6(x-12)=57 | | 3n+3(n+4)=42 | | 27x+-171=76+8x | | 159=-3x-3(-6x-18) | | (7x+27)+4x=(x+9)+(2x+154) | | 0=-5x+5(2x+6) | | -6x-15=7x+24 |